An evaluation of students' attitudes toward English language learning in terms of several variables - Gomleksiz, Mehmet Nuri (Elsevier Science Bv, 2010)
Age, socio-economic status, strategies, methods and techniques, teaching-learning environment and cultural dimension are some of the factors that affect English language learning. Attitudes towards language learning should also be taken into consideration. The purpose of this study is to explore students' attitudes towards learning English in terms of gender, grade level and department variables. Data were collected through a Likert-type scale from a total of 1275 students enrolled at F rat University, Turkey. ANOVA and t test were used to analyze the data. Statistically significant differences were observed in terms of gender, grade level and department variables. Some useful implications are discussed based on the research findings to help students develop positive attitude towards English language learning.
1st World Conference on Learning, Teaching and Administration (WCLTA) -- OCT 29-31, 2010 -- Amer Univ, Cairo, EGYPT
Keywords: English language learning; attitude; university; student